Medical Tourism in Mexico: An Economic Activity with Great Potential - FISCHER, Laura (Journal of Environmental Management and Tourism; Vol 13 No 6 (2022): JEMT, Volume XIII, Issue 6(62), Fall 2022, 2022)
Medical tourism is an activity that has become an attractive option for the economic growth of many countries. In the last ten years, this type of medical practice has been enhanced; currently the countries are increasing the attention of patients from abroad to raise the economic contribution, generating a social development, due to the impact on other service areas such as hotels, restaurants, transport, infrastructure among others. The objective of the work is to know the economic importance that health tourism has for Mexico, specifically medical tourism, its scope and limitations in terms of promotion of this sector by the government and private initiative. To this end, a bibliographic study was carried out on the subject. The results show that Mexico has great economic potential in this sector, already in 2018, the economic spillover exceeded 4 billion dollars and, with adequate promotion programs to attract more foreign patients, this amount could increase to 13.8 billion dollars by 2030. The government through the Ministry of Tourism, has detected the great importance in the sector, although it carries out some programs such as the Medical Tourism Congress, it is not carrying out sufficient promotional strategies to promote it worldwide